Association of oxidative stress and dynamic thiol‐disulphide homeostasis with atopic dermatitis severity and chronicity in children: a prospective study. (22nd November 2017) - Uysal, P.; Avcil, S.; Neşelioğlu, S.; Biçer, C.; Çatal, F.
Summary: Background: Oxidative stress (OS) has an important effect on the pathogenesis of atopic dermatitis (AD). Thiols are antioxidants that regulate intracellular redox metabolism and protect keratinocytes against OS damage in the stratum corneum. Aim: To investigate dynamic thiol‐disulphide homeostasis (dTDH) as a novel OS parameter in children with AD, and its relationship with disease severity and chronicity. Methods: Severity of AD was determined by using the instruments SCORing Atopic Dermatitis (SCORAD) and Eczema Area And Severity Index (EASI) upon enrolment in the study (SCORAD1 and EASI1 ) and after 1 year (SCORAD2 and EASI2 ). Native thiol, total thiol and disulphide levels were measured as novel OS parameters, and the ratios of disulphide/native thiol, disulphide/total thiol and native/total thiol were calculated as dTDH. Results: In the AD group, the serum disulphide level and the ratios of disulphide/native thiol and disulphide/total thiol were significantly lower than in healthy controls ( P  = 0.01, P  < 0.01 and P  < 0.01, respectively). There was no significant association between OS parameters and disease severity ( P  > 0.05). SCORAD2 and EASI2 were positively correlated with disulphide/native thiol ratio ( r  = 0.29, P  < 0.03 and r  = 0.35, P  < 0.01, respectively), whereas they were negatively correlated with the native/total thiol ratio ( r  = −0.30, P  = 0.02 for both). Conclusions: Both OS and impaired dTDH were found to be related to childhood AD. None of the OS parameters was associated with AD severity. dTDH is a possible diagnostic tool to predict AD chronicity.